Makna Nilai Tanggung Jawab Sebagai Pilar Pendidikan Karakter Mahasiswa - Tiara Suriyatna Mentaya; Latifah Mayasari; Muhammad Zaki Arrazin; sahduari, Sahduari (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This article reviews the importance of the value of responsibility as one of the main pillars in character education for students, especially in higher education. This value is not only important in the academic realm, but also becomes the moral and social basis in forming students with integrity. This research was conducted with a qualitative descriptive approach, using interview, observation, and documentation techniques on students of the Islamic Religious Education (PAI) Study Program class of 2022 at IAIN Palangka Raya. The findings show that responsibility in undergoing the learning process, time management, and discipline are important indicators in the internalization of character values. Students who have a sense of responsibility are able to complete academic tasks regularly, value time, and remain disciplined even when faced with challenges such as organizational activities or work. Therefore, systematic and continuous character building is needed to instill the value of responsibility as a whole in the campus environment.